Evaluación técnico-financiera del diseño de un sistema híbrido fotovoltaico como fuente de energía alternativa para el alumbrado de un campo de estudio en la cuenca Llanos Orientales (2018)
The present work of degree allows to study and financially evaluate technically the use of environmentally friendly technologies such as a hybrid photovoltaic system for the generation of electrical energy, in order to replace the conventional generators in the field of study. First, detailed the operation and operation of the electricity generators and the different technologies of photovoltaic hybrid systems used in innovative projects, and the cases of implementation in different fields of the world, then, a detailed description of the field of study was made and of all the parameters to take into account to finally implement photovoltaic solar energy technologies. A selection matrix was designed where, by means of specific parameters of four pilot fields, the most suitable for the implementation of the technology is selected and it can generate enough energy for the lighting of the study field, then the different variations were specified. and the characteristics of solar radiation in the field of study. Additionally, a qualitative evaluation of the different photovoltaic solar energy technologies was carried out and the most convenient one was chosen for the field of study. After this, it explains and describes the physical phenomena that explain the behavior and performance of the selected technology.